Réception et transformation des idées géographiques de ĽÉcole française de géographie au Japon - Nozawa, Hideki (Finisterra, 1998)
RECEPTION AND TRANSFORMATION OF GEOGRAPHICAL IDEAS OF THE FRENCH GEOGRAPHY SCHOOL IN JAPAN - The main characteristics of the geography of Vidal de La Blache and of his school of thought were known in Japan until the early days of the 1940's, especially through the efforts made by a professor of the University of Tokyo, Koji Iizuka. French geography was considered in Japan as representative of human geography in the world. It was used to counter Japanese geography, which was held to be environmentalistic and deterministic under the strong influence of German geography. After the Second World War, French geography offered an antithesis to fascist geography or to geopolitics during the movement of democratization in Japan, when geography was categorized as one of the disciplines of the social sciences. Two major elements played a role in the reconstruction of Japanese geography: the Vidalism tradition of French geography and the Marxist scientific environment. From the middle of the 1950's, Japanese geographers took an interest in the methodologies of French regional geography, for exemple the important notion of way of life. Paradoxically, they never wrote original regional monographs of Japan.